Cloning of Nitrate Reductase and Nitrite Reductase Genes and Their Functional Analysis in Regulating Cr(VI) Reduction in Ectomycorrhizal Fungus Pisolithus sp.1 - Shi, Liang; Liu, Binhao; Zhang, Xinzhe; Bu, Yuan; Shen, Zhenguo; Zou, Jianwen; Chen, Yahua (Frontiers in Microbiology, 2022)
Assimilatory-type nitrate reductase (NR) and nitrite reductase (NiR) are the key enzymes involving in nitrate assimilation and nitrogen cycling in microorganisms. NR and NiR with NADH or NADPH and FMN or FAD domains could be coupled to the reduction process of hexavalent chromium (Cr(VI)) in microorganisms. A new assimilatory-type NR gene (named niaD) and a new assimilatory-type NiR gene (named niiA) are cloned, identifed, and functionally characterized by 5’ and 3’ RACE, alignment, annotation, phylogenetic tree and yeast mutant complementation analyses from Pisolithus sp.1, a dominant symbiotic ectomycorrhizal fungi (EMF) that can assist in phytoremediation. Assimilatory-type niaD and niiA were 2754 bp and 3468 bp, and encode a polypeptide with 917 and 1155 amino acid residues, respectively. The isoelectric point of NR (Pisolithus sp.1 NR) and NiR (Pisolithus sp.1 NiR) of Pisolithus sp.1 are 6.07 and 6.38 respectively. The calculated molecular mass of Pisolithus sp.1 NR and Pisolithus sp.1 NiR are 102.065 and 126.914 kDa respectively. Yeast mutant complementation analysis, protein purification and activities of NR and NiR under Cr treatment suggest that Pisolithus sp.1 NR is a functional NR which mediate Cr(VI) tolerance and reduction. The multiple alignment demonstrates that Pisolithus sp.1 NR is potentially a nicotinamide adenine dinucleotide phosphate dependent flavin mononucleotide reductase, and also Class II chromate reductase. Our results suggest that Pisolithus sp.1 NR plays a key role in Cr(VI) reduction in the EMF Pisolithus sp.1.